The Euro-Team Early Pregnancy (ETEP)* protocol for recurrent miscarriage - Berry, C. W.; Brambati, B.; Eskes, T. K. A.B.; Exalto, N.; Fox, H.; Geraedts, J. P. M.; Gerhard, Ingrid; Gomes, F.Gonzales; Grudzinskas, J. G.; Hustin, J.; Jouppila, P.; Lindblom, B. K. A.; et al. (Human reproduction, 1995)
The underlying causes and rationale for treatment of recurrent abortion are not entirely clear. The Euro-Team early pregnancy protocol was developed as a diagnostic work-up based on the evaluation of risk factors. Possibilities for therapy can be based only on the expectancy that elimination of some risk factors may improve the prognosis.
Gesehen am 02.04.2025